(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article is about a business process. This article also mentions the main features of a business process; in the literature there are many definitions of the term “business process”, among them the main definitions are highlighted. Detailed information about the types of business processes is also provided. In addition, this article describes the purpose and objectives of describing and modeling business processes, as well as the sequence of methods for describing business processes, as well as the important aspects of the business process in each method, as well as productivity and quality. solutions to optimize activities.